The gaucho’s pilgrimage: from the Museum of Luján to the Creole Park and the Gaucho Museum in San Antonio de Areco (Quinto Sol, 2013)
This article explores the way in which certain cultural practices related to the construction of the myth of the gaucho and the exaltation of the creole feeling were reintroduced and modeled by government officers. Specifically, the article analyses experiences built around the representation and the exaltation of the figure of the gaucho in two different times and places: on the one hand, the room set up in his honor in 1925 in the Historical and Colonial Museum of the province of Buenos Aires, located in Luján and, on the other hand, the Creole Park and the Gaucho Museum “Ricardo Güiraldes”, inaugurated in 1937 in San Antonio de Areco. The materialization of both experiences involved heterogeneity of agents connected to civil associations, government departments, the historiographical field and mercantile activities, which supplied the material, social and cultural resources necessary to form collections of objects and to build spaces for their exhibition. However, while the first experience relied on scarce state funding, the second one added the explicit support of certain sectors of the ruling elite in Manuel Fresco’s conservative government.
Keywords: gaucho; Historical Museum of Luján; Creole Park; Gaucho Museum; San Antonio de Areco